1996
DOI: 10.1046/j.1365-2249.1996.d01-870.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of tumour necrosis factor-alpha (TNF-α) in host defence mechanism against Cryptococcus neoformans

Abstract: SUMMARYWe investigated the role of TNF-in the host defence mechanism against infection with a virulent strain of Cryptococcus neoformans. Administration of exogenous recombinant human TNF-significantly prolonged the survival time of mice infected by intratracheal instillation of the organism. Surprisingly, neutralizing MoAb to murine TNF-did not shorten their survival time, a finding inconsistent with previous results. To investigate the cause of this inconsistency, we examined the production of TNFin the lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
51
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 30 publications
6
51
1
Order By: Relevance
“…Consistent with our current studies, we have previously demonstrated that infection with the highly virulent cryptococcal strain 145A does not induce (i) TNF-␣ or IFN-␥ until later in the infection or (ii) protective T1 immunity (13,29). In addition, Kawakami and colleagues have reported that infection with the highly virulent C. neoformans strain YC-11 does not induce TNF-␣, IL-12, and IFN-␥ (18,19), but treatment of the mice with IL-12 stimulated IFN-␥ production in the lungs and protected them against infection (19).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our current studies, we have previously demonstrated that infection with the highly virulent cryptococcal strain 145A does not induce (i) TNF-␣ or IFN-␥ until later in the infection or (ii) protective T1 immunity (13,29). In addition, Kawakami and colleagues have reported that infection with the highly virulent C. neoformans strain YC-11 does not induce TNF-␣, IL-12, and IFN-␥ (18,19), but treatment of the mice with IL-12 stimulated IFN-␥ production in the lungs and protected them against infection (19).…”
Section: Discussionsupporting
confidence: 91%
“…8 -10 Quantitative differences in the expression of these factors have been shown to alter the host's ability to clear the primary infection or prevent systemic dissemination. [11][12][13][14][15] However, the specific cellular and molecular mechanisms by which these factors enhance virulence remain largely unknown. Understanding these mechanisms may aid the development of new strategies designed to prevent and/or treat invasive fungal disease in humans.…”
mentioning
confidence: 99%
“…Separation of supernatants by Con A affinity chromatography yields a highly mannosylated protein fraction termed mannoprotein (MP) 3 (14). MP can elicit delayed-type hypersensitivity reactions and induces production of the cytokines TNF-␣ (15), IL-12, and IFN-␥ (16), shown to be critical in decreasing fungal loads in murine models of cryptococcosis (17)(18)(19)(20). Moreover, T cells from patients who have recovered from cryptococcosis proliferate and secrete cytokines in response to MP (21,22).…”
mentioning
confidence: 99%